Cameron Ziashakeri: capstone - Ziashakeri, Cameron, artist (Colorado State University. Libraries, 2025)
The artist's statement: As a designer, I create with the goal of making ideas feel clear, meaningful, and visually engaging. I've always been drawn to the way design can solve problems, connect people, and turn complex messages into something simple and memorable. My work reflects a mix of curiosity, experimentation, and a genuine love for the creative process. I use Digital illustration, typography, layout design, branding systems, and hands-on sketching to explore how visuals can influence emotion and understanding. My process starts with getting to know the project, and more importantly, the people behind it. I take the time to understand my clients, their story, their goals, and what makes them unique. From there, I move into research, sketching, early concepts, refining ideas, and shaping a final design that feels thoughtful, functional, and true to who it's made for. I'm especially inspired by storytelling and the challenge of finding that "sweet spot" where meaning and creativity meet. I love creating designs that are unique and sometimes unexpected, a design that pushes beyond the ordinary while still staying aligned with purpose. There's a time and place for calm, familiar design, but thinking outside the box and crafting something that feels truly personal is what excites me most. If everything looks the same, then nothing feels special. Whether I'm working on branding, posters, packaging, or digital experiences, I strive to make my work intentional, human centered, and visually strong. Collaboration is at the front of what I do, and I enjoy guiding a project from the first ideas through exploration, revisions, and final execution, ensuring the end result not only looks great but genuinely meets the needs and goals of the people it's designed for. My body of work represents growth, problem-solving, and a commitment to creating design that leaves an impact, no matter the scale.
Colorado State University Art and Art History Department capstone project.
Capstone contains the artist's statement, a list of works, and images of works.
Keywords: graphic design